Monitoring the Early Antiproliferative Effect of the Analgesic–Antitumor Peptide, BmK AGAP on Breast Cancer Using Intravoxel Incoherent Motion With a Reduced Distribution of Four b-Values - Doudou, Natacha Raissa; Kampo, Sylvanus; Liu, Yajie; Ahmmed, Bulbul; Zeng, Dewei; Zheng, Minting; Mohamadou, Aminou; Wen, Qing-Ping; Wang, Shaowu (Frontiers in Physiology, 2019)
Background: The present study aimed to investigate the possibility of using intravoxel incoherent motion diffusion MRI to quantitatively assess the early therapeutic effect of analgesic-antitumor peptide, BmK AGAP on breast cancer and also evaluate the medical value of a reduced distribution of 4 b-values. Methods: IVIM diffusion MRI using 10 b-values and 4 b-values (0-1000 sec/mm2) was performed at 5 different time points on BALB/c mice bearing xenograft breast tumors treated with BmK AGAP. Variability in Dslow, Dfast, PF and ADC derived from the set of 10 b-values and 4 b-values, was assessed to evaluate the antitumor effect of BmK AGAP on breast tumor. Results: The data showed that PF values significantly decreased in rBmK AGAP treated mice on day 12 (P = 0.044). PF displayed the greatest AUC but with a poor medical value (AUC=0.65). The data showed no significant difference between IVIM measurements acquired from the two sets of b-values at different time points except in the PF on day 3. The within-subject coefficients of variation were relatively higher in Dfast and PF. However, except for a case noticed on day 0 in PF measurements, the results indicated no statistically significant difference at various time points in the rBmK AGAP treated or the untreated group (P <0.05). Conclusion: IVIM showed poor medical value in the early evaluation of the anti-proliferative effect of rBmK AGAP in breast cancer, suggesting sensitivity in PF. A reduced distribution of 4 b-values may provide remarkable measurements but with a potential loss of accuracy in the perfusion-related parameter PF.